Three months of Western diet induces small intestinal mucosa alteration in TLR KO mice. Issue 6 (17th January 2017) - Sardi, Claudia; Luchini, Patrizia; Emanuelli, Andrea; Giannoni, Amedeo; Martini, Elisa; Manara, Lucia M; Sfondrini, Lucia; Kallikourdis, Marinos; Sommariva, Michele; Rumio, Cristiano
Abstract: Several studies support the role of Western‐style diet (WD) in inflammatory bowel disease (IBD).Toll‐like receptors/NOD‐like receptors (TLRs/NLRs) are important to maintain a healthy epithelium as well as inducing inflammation. Given that dietary factors influence IBD development, that epithelial dysfunction is thought to be involved in initiating intestinal inflammation and that TLR‐NLR are involved in maintenance of the functionality of intestinal epithelium as well as in regulating inflammation, we decided to examine the role of TLR signals in the triggering events that lead to alteration of the small intestinal epithelium associated to consumption of WD. C57BL/6J mice deficient for TLR2, 4, 9, or NOD2 and wild‐type (WT) were fed a WD or a standard diet for 3 months. The effects of WD on small intestinal samples were evaluated by histological and immunohistochemical analysis. After 3 months, WD modifies the morphology and the organization of the small intestine in TLR9 KO mice compared with WT mice and the others TLRs. The most interesting change involved the expression of proliferative and differentiation markers of WNT signaling, Ki67 and FzD5. Mice deficient in TLR2, 4, and NOD2 have a significant reduction in the proliferative cell numbers but do not show any signs of histological alterations. Our results suggest that TLR9 is an important protective factor in intestinal epithelial homeostasis and provide new insights into an unrecognized role of TLR9 signaling in the small intestinal mucosa dysfunction associated with WD. Abstract : Diet has an impact on small intestine morphology TLRs participate in WD‐induced modification of intestine morphology TLR9 has a protective effect in WD‐induced gut alterations